Standardization of Rendang Lokan Recipes in Nagari Sasak, Sasak Ranah Pesisir Sub District, West Pasaman Regency - Fitri, Annisa Rahma; Gusnita, Wiwik (Universitas Negeri Padang, 2022)
This research is motivated by differences in the use of spices, the dosage of ingredients in processing and processing techniques of randang lokan so that there are differences in the quality of the results of randang. This study aims to standardize the recipe for randang lokan in Nagari Sasak, District of Sasak Ranah Pesisir, West Pasaman Regency which includes ingredients, spices, tools, processing techniques and analyzes the quality of randang lokan in terms of color, aroma, texture and taste. This type of research method is qualitative and quantitative research with mixed methods (Mixed Method). Qualitative data sources were obtained from 10 community members who were experts in making lokan rendang and quantitative data sources were obtained from 10 trained panelists, namely people who knew about rendang lokan and 5 limited panelists from UNP Catering lecturers. Qualitative data collection techniques are observation, interviews, documentation and quantitative data collection techniques are organoleptic test questionnaire format. The qualitative data analysis technique uses three activity lines, namely: data reduction, data presentation, drawing conclusions and quantitative data analysis techniques using the formula (Mx = Σ x / N), the validity of the quantitative data validity test data, namely: participation extension, diligent observation, and triangulation. Based on the results of the study, the best Randang Lokan recipe in Nagari Sasak, Sasak Ranah Pesisir District, West Pasaman Regency includes the ingredients used, the amount of ingredients, how to make and and the quality of Randang Lokan. From this recipe for randang lokan, the standardization of randang lokan has been converted. Organoleptic tests were carried out to standardize the recipe for randang lokan to obtain good quality meat, including: color of dadak randang lokan (dark brown), aroma of lokan (perfumed flavor), aroma of dadak randang lokan (charm typical of lokan inflammation), texture of lokan (tender), texture of dadak Randang lokan is quite dry, the taste of lokan (not fishy), the taste of sudden randang lokan (savory).